Preparation and application method of SrTiO3.Al-MgO / PSF-PVDF photocatalytic membrane
By preparing SRTIO3 · AL-MGO/PSF-PVDF optical catalytic film, the problem of poor stability and difficulty in separation and recycling of traditional photocatalysts, and realizing organic pollutants in the water body, with excellent anti-pollution and energy saving and environmental protection performance Essence
Patent Information
- Application Number
- CN202411452221.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-17
AI Technical Summary
Traditional photocatalysts exist in powder form, with small particles, easy to deactivate, poor stability, and difficult catalyst separation and recovery, making it difficult to efficiently remove organic pollutants in water bodies.
Adopt the preparation method of SRTIO3 · Al-MGO/PSF-PVDF optical catalytic film, to prepare optical catalyst nanoparticles such as thermal decomposition, solid-phase reaction method, water heat method, and non-original method, and it will be with the agglomeration and the agglomeration and the agglomeration and the agglomeration. Combining polytomone ethylene and other materials to prepare high -efficiency photocatalytic membranes.
It improves the removal efficiency of organic pollutants, enhances pollution resistance, energy saving and environmental protection performance, reduces system maintenance costs and energy consumption, and promotes the intelligent and green development of environmental purification technology.
Smart Images

Figure CN119346181A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method of a photocatalytic film and an application method thereof, and in particular to a preparation method of a SrTiO3·Al-MgO / PSF-PVDF photocatalytic film and an application method thereof. Background Art
[0002] In addition to inorganic pollutants, water bodies also contain a large amount of organic pollutants, which affect the ecosystem in the form of toxicity and reduction of dissolved oxygen in the water, and endanger human health. Specific organic pollutants refer to those organic compounds that are highly toxic, highly cumulative, difficult to degrade, and listed as priority pollutants. They are of many varieties and low in content. Organic pollutants refer to organic compounds that cause environmental pollution and have harmful effects on the ecosystem. They can be divided into two categories: natural organic pollutants and artificially synthesized organic pollutants. The former are mainly produced by the metabolic activities of organisms and other biochemical processes; such as chlortetracycline, ethyl carbamate, etc. The latter are produced with the rise of the modern synthetic chemical industry; such as plastics, synthetic fibers, dyes, coatings, pesticides, food additives, medicines, etc. For antibiotics, one of the organic pollutants, the harm caused to the human body is the most serious. For example: antibiotics enter the stomach through the mouth, are absorbed into the blood through the intestines and transported to various cells of the human body. Only the drugs that reach the lesion site can kill the pathogens. Drugs in other tissues not only fail to kill bacteria, but their metabolites must be excreted from the body through the liver and kidneys, which has a certain damaging effect on organs such as the liver and kidneys. For example, tetracycline and erythromycin all need to be metabolized in the liver.
[0003] Therefore, in order to ensure human health and the beautiful expectation of a green home, the degradation of antibiotic organic pollutants has become an important task. Photocatalytic degradation technology can degrade organic pollutants in antibiotics into non-toxic products by making photocatalysts produce species with strong oxidative activity under visible light irradiation, becoming a hot method to solve the problem of environmental pollution and harm to the human body caused by the abuse of antibiotics. Photocatalytic degradation technology is widely used in the treatment of organic pollutants because of its clean energy, wide range of applications, and no secondary pollution. However, traditional photocatalysts usually exist in the form of powders, with small particles, easy deactivation, poor stability, and difficult catalyst separation and recovery. Photocatalytic film is a new type of photocatalytic material that is highly efficient and can be used in continuous processes. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a SrTiO3·Al-MgO / PSF-PVDF photocatalytic membrane and its application method, which is a method based on a photocatalytic-membrane separation circulation system and a method for degrading organic pollutants in wastewater. Under the irradiation of visible light, the method degrades organic pollutants in wastewater, improves the removal efficiency and pollution resistance of pollutants, and has advantages in energy conservation and environmental protection. It reduces the maintenance cost and energy consumption of the system and promotes the development of environmental purification technology towards intelligence and greenness.
[0005] The technical solution adopted by the present invention is: A method for preparing a SrTiO3·Al-MgO / PSF-PVDF photocatalytic film, the method comprising the following steps: S1: Preparation of MgO photocatalyst nanoparticles by thermal decomposition: Mg(OH)2 is used as a precursor, and MgO is obtained by high-temperature calcination and decomposition, which is then ground and collected after cooling; S2: Preparation of SrTiO3 photocatalyst nanoparticles by solid phase reaction method: Strontium carbonate (SrCO3) and titanium dioxide (TiO2) are mixed and ground in a ball mill to make the reactants evenly distributed; the mixed powder is heated to 700-900°C to remove excess water and decompose the carbonate in the mixed powder; then, the pre-burned powder is further sintered at 1300-1500°C to form SrTiO3 with a complete crystal phase; after slow cooling, the powder is ground and collected; S3: Preparation of SrTiO3·Al photocatalyst nanoparticles by hydrothermal method: SrCl2, TiCl4 and AlCl3 are dissolved in a water solvent to form a mixed solution, the solution is adjusted to a pH value (greater than 13), and then the solution is transferred to an autoclave for a hydrothermal reaction at 150-250°C for 12-48 hours; during the reaction, SrTiO3 with a perovskite structure is gradually formed, and aluminum is doped into the lattice; after cooling, the product is taken out, washed, dried and further heat treated to improve the crystallinity; S4: Preparation of SrTiO3·Al-MgO photocatalyst nanoparticles by ex-situ method: The SrTiO3·Al powder was immersed in Mg(OH)2 aqueous solution, ultrasonicated for 120 min, centrifuged, dried and collected; the dried mixture was placed in a tube furnace and fired under the conditions of temperature of 600°C, firing time of 150 min and flow rate of 50 mL·min -1 (argon), SrTiO3·Al-MgO photocatalyst nanoparticles were prepared; S5: Preparation of MgO / PSF-PVDF, SrTiO3 / PSF-PVDF, SrTiO3·Al / PSF-PVDF, SrTiO3·Al-MgO / PSF-PVDF photocatalytic films: The base liquid of the photocatalytic membrane is as follows: MgO, SrTiO3, SrTiO3·Al, SrTiO3·Al-MgO photocatalyst particles are added to a mixture of polysulfone (PSF), polyvinylidene fluoride (PVDF), lithium chloride (LiCl), N,N-dimethylacetamide (DMAC) and ethylene glycol dimethyl ether (EGME); the mixture is stirred and mixed for 12 hours, filtered with a filter, and degassed with a vacuum pump; the degassed solution is evenly spread on a glass plate with a scraper to make it into a rectangular shape, and then the glass plate is immersed in a deionized water bath for 24 hours to prepare MgO / PSF-PVDF, SrTiO3 / PSF-PVDF, SrTiO3·Al / PSF-PVDF, SrTiO3·Al-MgO / PSF-PVDF photocatalytic membranes, respectively.
[0006] An application method of a SrTiO3·Al-MgO / PSF-PVDF photocatalytic film, the method comprising a photocatalytic film separation and degradation organic pollutant circulation system, the system comprising a liquid storage tank, a bypass pipe, a gear pump, a pressure gauge, a flow meter, a regulating valve, a xenon lamp and a photocatalytic film degradation device; The application process is as follows: Put organic pollutant wastewater into the liquid storage tank, adjust the pressure gauge and flow meter, cut the SrTiO3·Al-MgO / PSF-PVDF photocatalytic film into a circle with a radius of 3 cm, put it into the photocatalytic film degradation device and fix it, install a 300W xenon lamp just above the center of the photocatalytic film degradation device to ensure that the center of the xenon lamp coincides with the center of the photocatalytic film degradation device, and the middle part of the photocatalytic film degradation device is a circular light-transmitting quartz glass to provide visible light for the working process of the photocatalytic film degradation device; turn on the gear pump, and the gear pump rotates to generate negative pressure, so that the organic wastewater in the liquid storage tank is sucked into the circulation system, part of the organic wastewater flows back to the liquid storage tank from the bypass pipe, and part of it enters the photocatalytic film degradation device through the pressure gauge, and after the organic wastewater flows out of the photocatalytic film degradation device, it flows through the pressure regulating valve and the flow meter respectively, and finally returns to the liquid storage tank, and the circulation treatment is 150 minutes.
[0007] The application method of the SrTiO3·Al-MgO / PSF-PVDF photocatalytic film is described, wherein a photocatalytic film layer is provided in the photocatalytic film degradation device.
[0008] In the application method of the SrTiO3·Al-MgO / PSF-PVDF photocatalytic film, the pressure value of the pressure gauge is 0.2MP.
[0009] The application method of the SrTiO3·Al-MgO / PSF-PVDF photocatalytic film, wherein the flow meter value is 40 mL·min -1 .
[0010] In the application method of the SrTiO3·Al-MgO / PSF-PVDF photocatalytic film, the initial concentration of the organic pollutants in the wastewater is 5-15 mg / L; the organic pollutants are organic compounds.
[0011] In the application method of the SrTiO3·Al-MgO / PSF-PVDF photocatalytic film, the organic compound is chlortetracycline, streptomycin, or daqingmycin.
[0012] The beneficial effects of the present invention are: 1. The photocatalytic film prepared by the present invention provides an efficient, stable, environmentally friendly and economical solution for degrading organic pollutants. It not only improves the pollutant removal efficiency, but also reduces the loss and recovery difficulty of the catalyst, and can be used for a long time in a variety of environments. In addition, the photocatalytic film technology can be combined with other purification technologies to form a more complete pollution control system with strong adaptability, energy saving and environmental protection.
[0013] 2. The present invention uses a photocatalytic-membrane separation test to degrade organic pollutants, using photocatalysts under the irradiation of visible light to degrade organic pollutants in wastewater into small molecular products such as carbon dioxide and water.
[0014] 3. The present invention creatively provides a method for degrading organic pollutants by photocatalysis-membrane separation. In the photocatalytic reaction system, the generation of photogenerated electron-hole pairs, the separation and migration of electron-holes, and the generation of active species (such as •OH and •O2 - ), these active species can effectively oxidize and decompose organic pollutants. Ultimately, organic pollutants undergo a series of oxidative degradation reactions and are converted into non-toxic and harmless products such as water and carbon dioxide. Organic pollutants (such as dyes, pesticides, drug residues, etc.) are oxidized by hydroxyl radicals (•OH) and superoxide anions (•O2 - ) and the molecular structure is gradually destroyed. These highly oxidizing active species can oxidize CC, CH and other bonds in organic matter, causing macromolecules to degrade into smaller inorganic substances (such as carbon dioxide and water), or even completely mineralize.
[0015] 4. The innovation of this invention lies in the high efficiency of pollutant removal, the improvement of anti-pollution ability, the versatility of material design and the advantages in energy saving and environmental protection. This combination not only improves the effect of water treatment and air purification, but also reduces the maintenance cost and energy consumption of the system, and promotes the development of environmental purification technology towards intelligence and greenness. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 XRD diagram of SrTiO3, SrTiO3·Al, and SrTiO3·Al-MgO photocatalyst particles synthesized in Example 1 of the present invention; Figure 2 The SEM images of the SrTiO3, SrTiO3·Al, and SrTiO3·Al-MgO photocatalyst particles synthesized in Example 1 of the present invention; Figure 3 This is a cycle flow chart based on photocatalysis-membrane separation application in Example 1; Figure 4 This is a graph showing the effect of different membranes on the degradation rate of chlortetracycline pollutant in Example 2; Figure 5 This is a graph showing the effect of different amounts of SrTiO3·Al-MgO on the degradation rate of chlortetracycline in Example 2; Figure 6 This is a graph showing the effect of different MgO loading amounts on chlortetracycline degradation rates in Example 2; Figure 7 This is a graph showing the drop rate of SrTiO3·Al-MgO to pollutant concentration change in Example 2; Figure 8 This is a comparison chart of the cyclic application of SrTiO3·Al-MgO / PSF-PVDF photocatalytic film in Example 2. DETAILED DESCRIPTION Example 1
[0017] Photocatalyst particles for degrading organic pollutants in wastewater and preparation method of photocatalytic film (1) MgO preparation process Mg(OH)2 is used as a precursor and MgO is obtained by high-temperature calcination and decomposition, which is then ground and collected after cooling.
[0018] (2) SrTiO3 preparation process (solid phase reaction method) Take a certain proportion of strontium carbonate (SrCO3) and titanium dioxide (TiO2) and mix them evenly, then grind them in a ball mill to make the reactants evenly distributed. Heat the mixed powder to 700-900℃, remove excess water, and decompose the carbonate in the mixed powder. Then, take the pre-burned powder and further sinter it at 1300-1500℃ to form SrTiO3 with a complete crystal phase. After slow cooling, grind and collect the powder.
[0019] (3) Preparation process of SrTiO3·Al (hydrothermal method) SrCl2, TiCl4 and AlCl3 are dissolved in water or other solvents to form a mixed solution. After adjusting the pH value of the solution, the solution is transferred to an autoclave and subjected to a hydrothermal reaction at 150-250°C for 12-48 hours. During the reaction, SrTiO3 with a perovskite structure is gradually formed, and aluminum is doped into the lattice. After cooling, the product is taken out, washed, dried and further heat treated to improve the crystallinity.
[0020] (4) Preparation process of SrTiO3·Al-MgO (ex situ method) Take a certain amount of SrTiO3·Al powder and immerse it in Mg(OH)2 aqueous solution. After ultrasonic treatment for 120 minutes, centrifuge, dry and collect. The dried mixture is placed in a tube furnace and fired at a temperature of 600℃, a firing time of 150 minutes and a flow rate of 50mL·min -1 (argon) to obtain SrTiO3·Al-MgO photocatalyst nanoparticles.
[0021] (5) Preparation of MgO / PSF-PVDF, SrTiO3 / PSF-PVDF, SrTiO3·Al / PSF-PVDF, and SrTiO3·Al-MgO / PSF-PVDF photocatalytic films The base liquid of the photocatalytic film is as follows: different grams of MgO, SrTiO3, SrTiO3·Al, SrTiO3·Al-MgO photocatalyst particles are added to the mixed solution of polysulfone (PSF), polyvinylidene fluoride (PVDF), lithium chloride (LiCl), N,N-dimethylacetamide (DMAC) and ethylene glycol dimethyl ether (EGME), and the mixture is stirred and mixed for 12 hours, filtered with a filter, and degassed with a vacuum pump. The degassed solution is evenly spread on a glass plate with a scraper to make it rectangular, and then the glass plate is immersed in a deionized water bath for 24 hours to prepare MgO / PSF-PVDF, SrTiO3 / PSF-PVDF, SrTiO3·Al / PSF-PVDF, SrTiO3·Al-MgO / PSF-PVDF photocatalytic films respectively.
[0022] The photocatalyst particles synthesized in Example 1 were characterized by an X-ray powder diffractometer. The results showed that the synthesized photocatalyst particles were MgO, SrTiO3, SrTiO3·Al, SrTiO3·Al-MgO, respectively. Figure 1 .
[0023] The photocatalyst particles synthesized by the method of Example 1 were observed by scanning electron microscopy. The results showed that the synthesized nanoparticles were MgO, SrTiO3, SrTiO3·Al, SrTiO3·Al-MgO, Figure 2(a, b, c, d) show SEM images of MgO, SrTiO3, SrTiO3·Al, and SrTiO3·Al-MgO photocatalyst particles. As can be seen from Figure (a), the SEM image of the MgO sample shows that its particles present a regular polyhedral shape, with a particle size of about 100 nanometers, a relatively smooth surface, clear edges, and a high degree of crystallinity. There is a slight agglomeration phenomenon between some particles. In the SEM image, the surface of the MgO particles shows some cracks, which may be caused by stress release after high-temperature treatment. The particle size distribution is uneven, ranging from a few hundred nanometers to a few microns. From Figure (b), it can be seen that the morphology of the SrTiO3 catalyst is a block structure. From Figure (c), it is known that the morphology of the SrTiO3·Al catalyst is a cubic structure with a size of 1μm. The cubic particles in this figure are doped with metal aluminum. Figure (d) shows that the SEM image of the composite material shows regular SrTiO3 particles with a size of about 1 micron and a cubic shape. The particle surface is relatively flat. Al and MgO particles are distributed on the surface of SrTiO3 particles, and some particles are slightly agglomerated, indicating that the composite material is well bonded. Figure 2 . Example 2
[0024] Based on photocatalysis-membrane separation circulation system like Figure 3 As shown, a photocatalytic-membrane separation degradation circulation system is shown. Organic wastewater is placed in a liquid storage tank 1, and a pressure gauge 4 and a flow meter 5 are adjusted. The SrTiO3·Al-MgO / PSF-PVDF photocatalytic membrane is cut into a circle with a radius of 3 cm, and is placed in a photocatalytic membrane degradation device 8 and fixed. A 300W xenon lamp 7 is installed above the center of the photocatalytic membrane degradation device 8 to ensure that the center of the xenon lamp 7 coincides with the center of the photocatalytic membrane degradation device 8. The middle part of the photocatalytic membrane degradation device 8 is a circular light-transmitting quartz glass to provide visible light for the working process of the photocatalytic membrane degradation device 8. The gear pump 3 is turned on, and the gear pump 3 rotates to generate negative pressure, so that the organic wastewater in the liquid storage tank 1 is sucked into the circulation system, a part of the organic wastewater flows back to the liquid storage tank 1 from the bypass pipe 2, and a part of the organic wastewater flows into the photocatalytic membrane degradation device 8 through the pressure gauge 4. After the organic wastewater flows out of the photocatalytic membrane degradation device 8, it flows through the pressure regulating valve 6 and the flow meter 5 respectively, and finally returns to the liquid storage tank 1, and the circulation treatment is 150 minutes. Example 3
[0025] A method for degrading organic pollutants in wastewater The photocatalytic membrane separation circulation system based on Example 1 is used to degrade chlortetracycline in wastewater. The method is as follows: organic wastewater containing chlortetracycline is placed in the liquid storage tank 1, the pressure gauge 4 and the flow meter 5 are adjusted, the photocatalytic membrane is cut into a circle with a radius of 3 cm, and it is placed in the photocatalytic membrane degradation device and fixed. A 300 W xenon lamp 7 is installed above the photocatalytic membrane degradation device to ensure that the center of the xenon lamp coincides with the center of the photocatalytic membrane degradation device, and the micro gear pump 3 is turned on to start the circulation treatment for 150 minutes. By adjusting the pressure control valve 6, the pressure value of the circulation system pressure gauge is 0.2MP, and the flow meter is adjusted to 40mL·min -1 .
[0026] Organic pollutants can be chlortetracycline, streptomycin, and chlortetracycline. The following is an example of the degradation of chlortetracycline solution in wastewater.
[0027] The concentration of chlortetracycline was measured using a UV-Vis spectrophotometer at a wavelength of K = 200-600 nm, and the results showed that the maximum absorption peak was near 369 nm. The linear relationship between concentration and absorbance was obtained by measuring the standard curve of concentration and absorbance.
[0028] Degradation rate (%) = (C0-C t ) / C0×100% Where C0 is the initial concentration of chlortetracycline (mg / L), C t It is the instantaneous concentration (mg / L) after a certain degradation time (T).
[0029] 1. Effect of different types of membranes on the degradation rate of chlortetracycline pollutant in wastewater Method: Add 5 mg / L chlortetracycline simulated wastewater to the storage tank 1, adjust the pressure gauge 4 and flow meter 5, cut the photocatalytic membrane into a circle with a radius of 3 cm, put it into the photocatalytic membrane degradation device and fix it. A 300 W xenon lamp 7 is installed above the photocatalytic membrane degradation device to ensure that the center of the xenon lamp coincides with the center of the photocatalytic membrane degradation device. Start the micro gear pump 3 to start the circulation treatment for 150 minutes. By adjusting the pressure control valve 6, the pressure value of the circulation system pressure gauge is 0.2MP, and the flow meter is adjusted to 40mL·min -1 .
[0030] The types of photocatalytic membranes are MgO / PSF-PVDF photocatalytic membrane, SrTiO3 / PSF-PVDF photocatalytic membrane, SrTiO3·Al / PSF-PVDF photocatalytic membrane and SrTiO3·Al-MgO / PSF-PVDF photocatalytic membrane. The degradation effects of different types of membranes on chlortetracycline simulated wastewater are shown in Figure 2. Figure 4 As shown. Figure 4It can be seen that as the cycle time increases, the degradation efficiency of each type of membrane is increasing. The SrTiO3·Al-MgO / PSF-PVDF photocatalytic membrane has the highest efficiency in degrading chlortetracycline in wastewater, which can reach 91.51% at 150 minutes. The present invention prefers SrTiO3·Al-MgO / PSF-PVDF photocatalytic membrane.
[0031] 2. Effect of different dosages of SrTiO3·Al-MgO photocatalyst on the degradation rate of chlortetracycline in wastewater Method: Add 5 mg / L chlortetracycline simulated wastewater to the storage tank 1, adjust the pressure gauge 4 and the flow meter 5, cut the photocatalytic membrane into a circle with a radius of 3 cm, put it into the photocatalytic membrane degradation device and fix it. A 300 W xenon lamp 7 is installed above the photocatalytic membrane degradation device to ensure that the center of the xenon lamp coincides with the center of the photocatalytic membrane degradation device. Start the micro gear pump 3 to start the circulation treatment for 150 minutes. By adjusting the pressure control valve 6, the pressure value of the circulation system pressure gauge is 0.2MP, and the flow meter is adjusted to 40mL·min -1 .
[0032] The dosage of SrTiO3·Al-MgO catalyst was 0.1g, 0.2g, 0.3g and 0.4g respectively. The degradation effect of SrTiO3·Al-MgO / PSF-PVDF photocatalytic film on chlortetracycline in wastewater was as follows: Figure 5 As shown. Figure 5 It can be seen that with the extension of the cycle time, the chlortetracycline degradation efficiency of each SrTiO3·Al-MgO dosage is increasing. The SrTiO3·Al-MgO / PSF-PVDF photocatalytic membrane using 0.3g SrTiO3·Al-MgO is the most efficient for degrading chlortetracycline in wastewater, which can reach 91.51% at 150min. The present invention preferably uses 0.3g of SrTiO3·Al-MgO photocatalyst particles to prepare SrTiO3·Al-MgO / PSF-PVDF photocatalytic membrane.
[0033] 3. Effect of different MgO loadings on the degradation rate of chlortetracycline in wastewater Method: Add 5 mg / L chlortetracycline simulated wastewater to the storage tank 1, adjust the pressure gauge 4 and the flow meter 5, cut the photocatalytic membrane into a circle with a radius of 3 cm, put it into the photocatalytic membrane degradation device and fix it. A 300 W xenon lamp 7 is installed above the photocatalytic membrane degradation device to ensure that the center of the xenon lamp coincides with the center of the photocatalytic membrane degradation device. Start the micro gear pump 3 to start the circulation treatment for 150 minutes. By adjusting the pressure control valve 6, the pressure value of the circulation system pressure gauge is 0.2MP, and the flow meter is adjusted to 40mL·min -1 .
[0034] The loading amounts of MgO were 3%, 4%, 5% and 6% respectively. The degradation effects of different MgO loading amounts on chlortetracycline in wastewater were as follows: Figure 6 As shown. Figure 6 It can be seen that when the MgO loading is 3%, 4%, 5% and 6%, the degradation efficiency of chlortetracycline is improved with the extension of the cycle time. When the MgO loading is 5%, the prepared SrTiO3·Al-MgO / PSF-PVDF photocatalytic film is used to degrade chlortetracycline in wastewater with the highest efficiency, which can reach 91.51% at 150 min. The preferred MgO loading of the present invention is 5%.
[0035] 4. Effect of pollutant concentration on the efficiency of SrTiO3·Al-MgO / PSF-PVDF photocatalytic membrane in the degradation of chlortetracycline in wastewater Method: Add chlortetracycline simulated wastewater to the liquid storage tank 1, adjust the pressure gauge 4 and flow meter 5, cut the photocatalytic membrane into a circle with a radius of 3 cm, put it into the photocatalytic membrane degradation device and fix it. A 300 W xenon lamp 7 is installed above the photocatalytic membrane degradation device to ensure that the center of the xenon lamp coincides with the center of the photocatalytic membrane degradation device. Start the micro gear pump 3 to start the circulation treatment for 150 minutes. By adjusting the pressure control valve 6, the pressure value of the circulation system pressure gauge is 0.2MP, and the flow meter is adjusted to 40mL·min -1 .
[0036] The effect of SrTiO3·Al-MgO / PSF-PVDF photocatalytic membrane on the degradation of chlortetracycline at different concentrations in wastewater is shown in Figure 2. Figure 7 As shown in the figure, the concentrations of chlortetracycline simulated wastewater are 5 mg / L, 10 mg / L and 15 mg / L respectively. Figure 7 It can be seen that as the circulation time increases, the degradation efficiency of chlortetracycline simulated wastewater of different concentrations increases. When the concentration of chlortetracycline simulated wastewater is 5 mg / L, the degradation efficiency is the highest, reaching 91.51% at 150 min. The preferred concentration of chlortetracycline simulated wastewater in the present invention is 5 mg / L.
[0037] (V) Cyclic test of SrTiO3·Al-MgO / PSF-PVDF photocatalytic film Method: Add 5mg / L chlortetracycline simulated wastewater to the liquid storage tank 1, adjust the pressure gauge 4 and the flow meter 5, cut the photocatalytic membrane into a circle with a radius of 3 cm, put it into the photocatalytic membrane degradation device and fix it. A 300 W xenon lamp 7 is installed above the photocatalytic membrane degradation device to ensure that the center of the xenon lamp coincides with the center of the photocatalytic membrane degradation device. Start the micro gear pump 3 to start the circulation treatment for 150min. By adjusting the pressure control valve 6, the pressure value of the circulation system pressure gauge is 0.2MP, and the flow meter is adjusted to 40mL·min -1 .
[0038] Figure 8 The figure shows the SrTiO3·Al-MgO / PSF-PVDF photocatalytic membrane undergoing a cycle test, under the conditions that the dosage of SrTiO3·Al-MgO is 0.3g, the loading amount of MgO is 5%, and the concentration of chlortetracycline in the simulated wastewater is 5mg / L. A cycle is performed every 150 minutes, for a total of four cycles. It can be seen from the figure that after four cycles, the degradation capacity can still reach 83.38%, indicating that the SrTiO3·Al-MgO / PSF-PVDF photocatalytic membrane can still maintain a high photocatalytic performance after four cycles.
Claims
1. A method for preparing a SrTiO3·Al-MgO / PSF-PVDF photocatalytic film, characterized in that: The method comprises the following steps: S1: Preparation of MgO photocatalyst nanoparticles by thermal decomposition: Mg(OH)2 is used as a precursor, and MgO is obtained by high-temperature calcination and decomposition, which is then ground and collected after cooling; S2: Preparation of SrTiO3 photocatalyst nanoparticles by solid phase reaction method: Strontium carbonate (SrCO3) and titanium dioxide (TiO2) are mixed and ground in a ball mill to make the reactants evenly distributed; the mixed powder is heated to 700-900°C to remove excess water and decompose the carbonate in the mixed powder; then, the pre-burned powder is further sintered at 1300-1500°C to form SrTiO3 with a complete crystal phase; after slow cooling, the powder is ground and collected; S3: Preparation of SrTiO3·Al photocatalyst nanoparticles by hydrothermal method: SrCl2, TiCl4 and AlCl3 are dissolved in a water solvent to form a mixed solution, the solution is adjusted to a pH value (greater than 13), and then the solution is transferred to an autoclave for a hydrothermal reaction at 150-250°C for 12-48 hours; during the reaction, SrTiO3 with a perovskite structure is gradually formed, and aluminum is doped into the lattice; after cooling, the product is taken out, washed, dried and further heat treated to improve the crystallinity; S4: Preparation of SrTiO3·Al-MgO photocatalyst nanoparticles by ex-situ method: The SrTiO3·Al powder was immersed in Mg(OH)2 aqueous solution, ultrasonicated for 120 min, centrifuged, dried and collected; the dried mixture was placed in a tube furnace and fired under the conditions of temperature of 600°C, firing time of 150 min and flow rate of 50 mL·min -1 (argon), SrTiO3·Al-MgO photocatalyst nanoparticles were prepared; S5: Preparation of MgO / PSF-PVDF, SrTiO3 / PSF-PVDF, SrTiO3·Al / PSF-PVDF, SrTiO3·Al-MgO / PSF-PVDF photocatalytic films: The base liquid of the photocatalytic membrane is as follows: MgO, SrTiO3, SrTiO3·Al, SrTiO3·Al-MgO photocatalyst particles are added to a mixture of polysulfone (PSF), polyvinylidene fluoride (PVDF), lithium chloride (LiCl), N,N-dimethylacetamide (DMAC) and ethylene glycol dimethyl ether (EGME); the mixture is stirred and mixed for 12 hours, filtered with a filter, and degassed with a vacuum pump; the degassed solution is evenly spread on a glass plate with a scraper to make it into a rectangular shape, and then the glass plate is immersed in a deionized water bath for 24 hours to prepare MgO / PSF-PVDF, SrTiO3 / PSF-PVDF, SrTiO3·Al / PSF-PVDF, SrTiO3·Al-MgO / PSF-PVDF photocatalytic membranes, respectively.
2. An application method of SrTiO3·Al-MgO / PSF-PVDF photocatalytic film, characterized in that: The method comprises a photocatalytic membrane separation and degradation organic pollutant circulation system, the system comprising a liquid storage tank (1), a bypass pipe (2), a gear pump (3), a pressure gauge (4), a flow meter (5), a regulating valve (6), a xenon lamp (7) and a photocatalytic membrane degradation device (8); The application process is as follows: The organic pollutant wastewater is placed in the liquid storage tank (1), the pressure gauge (4) and the flow meter (5) are adjusted, the SrTiO3·Al-MgO / PSF-PVDF photocatalytic film is cut into a circle with a radius of 3 cm, and is placed in the photocatalytic film degradation device (8) and fixed. A 300W xenon lamp (7) is installed above the center of the photocatalytic film degradation device (8), ensuring that the center of the xenon lamp (7) coincides with the center of the photocatalytic film degradation device (8). The middle part of the photocatalytic film degradation device (8) is a circular light-transmitting quartz glass. Visible light is provided for the working process of the photocatalytic membrane degradation device (8); the gear pump (3) is turned on, and the gear pump (3) rotates to generate negative pressure, so that the organic wastewater in the liquid storage tank (1) is sucked into the circulation system, a part of the organic wastewater flows back to the liquid storage tank (1) from the bypass pipe (2), and a part of the organic wastewater enters the photocatalytic membrane degradation device (8) through the pressure gauge (4); after the organic wastewater flows out of the photocatalytic membrane degradation device (8), it flows through the pressure regulating valve (6) and the flow meter (5) respectively, and finally returns to the liquid storage tank (1), and the circulation treatment is completed for 150 minutes.
3. The application method of the SrTiO3·Al-MgO / PSF-PVDF photocatalytic film according to claim 2, characterized in that: The photocatalytic film degradation device (8) is provided with a photocatalytic film layer.
4. The method for applying the SrTiO3·Al-MgO / PSF-PVDF photocatalytic film according to claim 2, characterized in that: The pressure value of the pressure gauge (4) is 0.2 MPa.
5. The application method of the SrTiO3·Al-MgO / PSF-PVDF photocatalytic film according to claim 2, characterized in that: The flow meter (5) value is 40 mL min -1 .
6. The method for applying the SrTiO3·Al-MgO / PSF-PVDF photocatalytic film according to claim 2, characterized in that: In the wastewater containing organic pollutants, the initial concentration of organic pollutants is 5-15 mg / L; the organic pollutants are organic compounds.
7. The application method of the SrTiO3·Al-MgO / PSF-PVDF photocatalytic film according to claim 6, characterized in that: The organic compounds are chlortetracycline, streptomycin and daqingmycin.
Citation Information
Patent Citations
Preparation method and applications of SrTiO3 / CdS heterojunction material
CN104971743A
MgO microsphere with high specific surface area and preparation method and application thereof
CN110950421A